2021
DOI: 10.1299/jamdsm.2021jamdsm0040
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of residual strains as a parameter of matrix cracking in CFRP laminates

Abstract: Matrix cracking in CFRP laminates results in degradation of mechanical properties of the material and appearance of residual strains. In this study, the residual strains are investigated experimentally and analytically for CFRP [0/75 6 ] s laminates. The typical stress-strain curves of cracked CFRP always show the presence of residual strain, a nonrecoverable strain in the laminates as the strain does not return to 0% even after being unloaded back to 0 MPa. This is a phenomenon where the matrix cracking in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Also, the typical stress-strain curves of cracked CFRP laminates always display unrecoverable strain in the laminates because the strain does not return to 0% even after being unloaded to 0 MPa. This is a phenomenon where matrix cracking in laminates allows the residual strain to appear due to the relaxation of curing stresses [38]. This phenomenon can also be observed in this study's results, as the strain becomes more evident due to the presence of crack in the resin pocket in the middle of the CFRP.…”
Section: Effects Of Thermal Residual Stresssupporting
confidence: 77%
See 2 more Smart Citations
“…Also, the typical stress-strain curves of cracked CFRP laminates always display unrecoverable strain in the laminates because the strain does not return to 0% even after being unloaded to 0 MPa. This is a phenomenon where matrix cracking in laminates allows the residual strain to appear due to the relaxation of curing stresses [38]. This phenomenon can also be observed in this study's results, as the strain becomes more evident due to the presence of crack in the resin pocket in the middle of the CFRP.…”
Section: Effects Of Thermal Residual Stresssupporting
confidence: 77%
“…To consider the strain change due to the temperature change during the curing process, the curing temperature and testing (room) temperature were set to 130ºC and 24ºC, respectively. The coefficients of thermal expansion (CTE) quoted from Fikry et al [38] are shown in Table 2.…”
Section: Finite Element Methods (Fem) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Unraveling this complexity necessitates a meticulous examination of micro-scale deformation distribution preceding the manifestation of each distinct type of damage. A thorough investigation into the nuanced aspects of deformation is imperative to gain insights into the material's response under diverse loading conditions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%